An Interdisciplinary Population Health Approach to the Radon Health Risk Management in Canada - Khan, Selim M.; Gomes, James (Université d'Ottawa | University of Ottawa, 2018)
Radon is a known carcinogen found in indoor air that exists at higher than the federal reference level (200 Bq/m3) in about 10% of Canadian homes. Every year, over 3,000 people die from radon-induced lung cancer, which accounts for 16% of annual lung cancer deaths in Canada. Radon is the leading cause of lung cancer deaths among non-smokers and is second among smokers. Children, women, and smokers from lower in-come groups are disproportionately affected. Although the Federal Government has re-set the guideline (from the previous 600 Bq/m3 down to 200 Bq/m3) and provincial governments revised the building codes to limit exposure, there remain controversies with the latest scientific development in adopting strategies of radon management in Canada. This review applies an Integrated Population Health Framework to look at the relation-ships and interactions between population health determinants such as biology and genetics, environment and occupation, and social and economic factors, that influence the health risk of radon. The evidence gathered supports policy analysis with the application of ethical and risk management principles that lead to the identification of efficient and affordable broad-based and population-level preventive strategies. The final inferences enhance the framework by adding critical intervention modalities to Health Canada’s National Radon Program.
Keywords: radon; public health risk; determinants of health; population health principles; interdisciplinary approach